An Exploration of Online Students’ Impressions of Contextualization, Segmentation, and Incorporation of Light Board Lectures in Multimedia Instructional Content - Sheryne M. Southard; Karen Young (Journal of Public and Professional Sociology)
The body of research indicates that content-specific and pedagogically-intentional multimedia is a valuable teaching tool for facilitating student learning. Numerous factors must be considered in the development of instructional multimedia that is designed to improve student outcomes. This qualitative and quantitative empirical study analyzes how contextualization, segmentation and the incorporation of light board lectures improves the student learning experience. This study provides University administrators, instructional designers and faculty with insight on the cost-benefit ratio of the development of instructional multimedia that incorporates these features.